ChemInform Abstract: In situ Slow Release of Isocyanates: Synthesis and Organocatalytic Application of N‐Acylureas. Issue 1 (7th January 2014) - Singh, Atul K.; Chawla, Ruchi; Yadav, Lal Dhar S.
Abstract A novel synthesis of symmetrical and unsymmetrical N‐acylureas is developed involving in situ formation of isocyanates from carboxamides with N, N‐dibromo‐p‐toluenesulfonamide.